MOBILE PROMOTION: PUSH-NOTIFICATION BY E-COMMERCE APPS, ARE YOU BEING IMPULSIVE WHEN YOU GET A PROMO? - Adyka Fajar Anugrah; Fahriza Rizki Pratama; Syarif Achmad Hidayatullah (POLITEKNIK PIKSI GANESHA, 2023)
had instant access to so many people, as more and more people use their phones as remotes for their everyday lives. As a result, marketing through mobile promotion can be a way for marketers to take advantage of this technology. One way to use mobile promotion can be done through push notifications to reach interaction and engagement with consumers. This study describes the effect of price discounts and scarcity on impulse buying tendencies which are moderated by the availability of money and availability of time. Data was collected from 236 respondents who are consumers of five e- commerce applications in Indonesia. In evaluating our proposed research, we used SEM to validate hypotheses, CFA and the Alpha Cronbach Coefficient to evaluate item validity and reliability. The results of the study show that discount prices and scarcity have a positive effect on impulse buying tendencies. Although discounts and scarcity have a positive effect on impulse buying tendencies, situational characteristics through availability of money and availability of time do not moderate the positive effect of impulse buying tendencies. These findings provide theoretical implications and understanding of patterns of impulse buying tendencies in mobile promotions through the use of push notifications.